2022
DOI: 10.1038/s41591-022-01737-y
|View full text |Cite
|
Sign up to set email alerts
|

In vivo topical gene therapy for recessive dystrophic epidermolysis bullosa: a phase 1 and 2 trial

Abstract: Recessive dystrophic epidermolysis bullosa (RDEB) is a lifelong genodermatosis associated with blistering, wounding, and scarring caused by mutations in COL7A1, the gene encoding the anchoring fibril component, collagen VII (C7). Here, we evaluated beremagene geperpavec (B-VEC), an engineered, non-replicating COL7A1 containing herpes simplex virus type 1 (HSV-1) vector, to treat RDEB skin. B-VEC restored C7 expression in RDEB keratinocytes, fibroblasts, RDEB mice and human RDEB xenografts. Subsequently, a rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 45 publications
0
47
0
5
Order By: Relevance
“…Investigation of topical gene therapy has also been done by Gurevich et al . [ 104 ] for recessive dystrophic epidermolysis bullosa (RDEB), which is caused by mutations in the COL7A1 gene that normally encodes for collagen VII (C7). They investigated beremagene geperpavec (B-VEC), a replication defective HSV-1 vector containing two copies of the COL7A1 coding sequence .…”
Section: Overview Of New Therapies In Development For Ichthyosismentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of topical gene therapy has also been done by Gurevich et al . [ 104 ] for recessive dystrophic epidermolysis bullosa (RDEB), which is caused by mutations in the COL7A1 gene that normally encodes for collagen VII (C7). They investigated beremagene geperpavec (B-VEC), a replication defective HSV-1 vector containing two copies of the COL7A1 coding sequence .…”
Section: Overview Of New Therapies In Development For Ichthyosismentioning
confidence: 99%
“…The results of Gurevich et al . [ 104 ] regarding B-VEC for RDEB patients as described above, were further investigated in a phase I/II trial. In this trial, nine RDEB patients received B-VEC treatment.…”
Section: Overview Of New Therapies In Development For Ichthyosismentioning
confidence: 99%
“…In addition, epidermolysis bullosa (EB) is a severe skin disease associated with skin fragility, which is caused by different genetic mutations of some genes involved in regulating adhesion of basal epidermal cells to the underlying basement membrane ( Jackson et al, 2017 ; Alharthi et al, 2021 ). Therefore, gene therapeutic strategies linked to EB can be applied to induce tissue regeneration of EB skin lesions or prevent EB-indued wound healing abnormalities ( Marinkovich and Tang, 2019 ; Gurevich et al, 2022 ). In this context, eenetically modified skin-derived stem cells have great potential as successful cell-based gene delivery systems locally or systemically.…”
Section: Regeneration and Repair Of Skin Woundsmentioning
confidence: 99%
“…Most approaches under study for EB therefore focus on topical treatment [ 109 ], either by topical compound delivery (e.g., in vivo gene-addition by viral [ 110 ] or minicircle non-viral vectors [ 111 ], antisense oligonucleotides [ 112 ]), ex vivo gene-replacement or gene-correction followed by injection of corrected fibroblasts [ 113 ], or the transplantation of large epidermal sheets cultured from ex vivo -corrected keratinocytes [ 114 , 115 , 116 , 117 ], analogous to the treatment of full-thickness burn-wounds [ 118 ]. In 2017, Hirsch et al reported a 7-year-old boy with laminin 332-deficient JEB in whom almost the entire epidermis (~0.85 m 2 ) was replaced using exogenously corrected, autologous skin grafts [ 119 , 120 ].…”
Section: Revertant Mosaicism As Treatment For Genodermatosesmentioning
confidence: 99%